Physical Activity after Cardiac EventS (PACES): a group education programme with subsequent text message support designed to increase physical activity in individuals with diagnosed coronary heart disease: a randomised controlled trial - Melanie J Davies; Kamlesh Khunti; Laura J Gray; Thomas Yates; Helen Dallosso; Samuel Seidu; Alex V Rowlands; Patrick J Highton; Louisa Y Herring; Sally Schreder; Emily J Smith; Ghazala Waheed; et al. (Open Heart)
Aim To assess the effectiveness of a low-cost pragmatic intervention (structured education and ongoing text message support) to increase daily physical activity in participants 12–48 months after a coronary heart disease cardiac event (myocardial infarction, angina or acute coronary syndrome) diagnosis.Methods A single-centre randomised controlled trial of 291 adults randomised to a structured education programme (n=145) or usual care (n=146). The programme consisted of two 2.5 hour sessions delivered 2 weeks apart, followed by supplementary text message support. The GENEActiv accelerometer assessed the primary outcome at 12 months (change in overall physical activity (expressed in milli gravitational (mg) units) from baseline). Secondary outcomes included anthropometric, physical function, cardiovascular, biochemical and patient-reported outcome measures. Linear regression was used to compare outcome measures between groups on a modified intention-to-treat basis.Results Participants’ mean age was 66.5±9.7 years, 84.5% males, 82.5% white British and 15.5% south Asian. At 12 months, there was no difference between the groups in terms of change in overall physical activity (−0.23 mg (95% CI −1.22 to 0.75), p=0.64) and the programme was well accepted (88% attendance). Exploratory analyses showed that average moderate to vigorous physical activity (MVPA) levels increased in individuals not meeting physical activity guidelines (≥150 min per week) on enrolment compared with those who did, by 8 minutes per day (8.04 (95% CI 0.99 to 15.10), p=0.03).Conclusion The programme was well attended but showed no change in physical activity levels. Results show high baseline MVPA levels and suggest that Physical Activity after Cardiac EventS education may benefit cardiac patients not currently meeting activity guidelines.Trial registration number ISRCTN91163727.